Partial diallel crosses for predicting yield of semiexotic maize populations - Silva, C. M.; Miranda Filho, J. B.; Mendes, U. C. [UNESP]; Reis, E. F. (Funpec-editora, 2017)
In Brazil, the total production of maize has increased continuously due to the advances in technology but also to the new frontiers for the maize crop, including the expansion of the second crop (safrinha; usually maize after soybean). Therefore, the exploitation of new sources of germplasm seems to be imperative to attend the actual and future demands for modern cultivars adapted to the greatly variable environments available to the maize crop. The present study was based on a partial diallel (intergroup) cross to provide quantitative information on the potential of two groups of varieties (NAP-exotics and HG-local) and their combining abilities to direct the synthesis of new populations to be used in hybrid crosses or as a base for breeding programs. The experiments were carried out in two planting seasons (safra-1st crop; safrinha-2nd crop) following the completely randomized block design with four replications of plots 5 m long spaced 0.9 m with 25 plants per plot after thinning. The following traits were analyzed: male flowering (days), stalk diameter (mm), plant height (m), ear height (m), tassel length (cm), tassel branch number, ear length (cm), ear diameter (cm), ear yield (t/ha), and grain yield (t/ha). The populations under study presented acceptable levels for yield potential and agronomic traits, thus assuring good perspectives for their use in breeding programs. The prediction for the new populations to be synthesized from the cross between the two groups of varieties contributed positively and HG-3 population was the most appropriate, in both eras, as the parent variety most promising in Group II (HG to be used as a base) for incorporation of varieties of Group I (NAP).
Keywords: Diallel analysis; Genetical enhancement; Prediction of composites